Multiple clay shoveler's fractures of the thoracic spine - Hoong, Wilbur Teng Jun (2023)
Typically, a clay shoveler's fracture is a stress-type avulsion fracture involving the spinous processes of the lower cervical or upper thoracic vertebrae. Even though C7 and T1 are the most commonly involved spinal levels, these avulsion fractures can occur at any lower cervical or upper thoracic level, either as solitary or multiple fractures. This fracture used to be common in workers who shovel heavy loads of clay for long periods, hence its name. It does not cause any structural, functional, or neurological impairments and is therefore considered a stable fracture. Management is mostly conservative, involving rest, analgesics, and activity modification for a period of 4-6 weeks. Here, we present a 35-year-old male who sustained a motor vehicle accident. Except for midline tenderness in the back, there were no other positive findings. Plain radiographs showed a T11 vertebral compression fracture and absent or deviated spinous process shadows for most of the upper thoracic vertebrae. Computed tomography (CT) imaging clearly revealed multiple spinous process fractures extending from T2 to T8 levels. Considering the stability of these fractures, the patient was managed conservatively with rest, bracing, and analgesics. The recovery was quick, and he was back to his full functional status by six weeks.